1999
DOI: 10.2466/pr0.1999.84.2.497
|View full text |Cite
|
Sign up to set email alerts
|

Hardiness and Major Personality Factors

Abstract: This study tested Maddi and Khoshaba's 1994 hypothesis that Hardiness is an index of mental health. A sample of 241 undergraduates (103 men and 138 women) completed the Dispositional Resilience Scale, the Revised NEO Personality Inventory, and the Psychopathology-5 Scales. Using the individual median scores on the three subscales (Commitment, Control, and Challenge) of the Dispositional Resilience Scale, the High Hardiness group was obtained by identifying the individuals who scored above the medians on all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 7 publications
1
16
0
2
Order By: Relevance
“…Different responses to this disruption lead to different outcomes, including resilience increasing, a return to baseline balance and a lower level of resilience (Richardson, 2002). Highly resilient individuals have the psychological capacity to rebound from negative circumstances and are more likely to find positive meaning in their negative circumstances, which promotes positive emotions (Ramanaiah, Sharpe, & Byravan, 1999; Richardson, 2002; Stajduhar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Different responses to this disruption lead to different outcomes, including resilience increasing, a return to baseline balance and a lower level of resilience (Richardson, 2002). Highly resilient individuals have the psychological capacity to rebound from negative circumstances and are more likely to find positive meaning in their negative circumstances, which promotes positive emotions (Ramanaiah, Sharpe, & Byravan, 1999; Richardson, 2002; Stajduhar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Maddi and Khoshaba theorized that hardiness was an index of mental health [Maddi and Khoshaba, 1994] and recent data has supported this hypothesis [Ramanaiah et al, 1999]. Tsuang [2000] has emphasized the substantial clinical implications that follow a better understanding of the forces that mould resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Maddi and Khoshaba (1994), for example, found that hardiness scores were negatively related to a number of Minnesota Multiphasic Personality Inventory (MMPI) scores showing psychopathological tendencies, supporting the hypothesis that hardiness may reflect a common denominator of mental health. Similarly, Ramanaiah and Sharpe (1999) found that subjects scoring high and low on hardiness differed in their scores on several psychopathology scales. Florian, Mikulincer, and Taubman (1995) found that hardiness instruments administered to 276 Israeli Army recruits predicted mental health at the end of a demanding, 4-month combat training period.…”
mentioning
confidence: 85%